Economics of Banana Cultivation in Trichur District - Indira Devi P (Department of Agricultural Economics, College of Horticulture, 1983)
This investigation on economics of banana cultivation in Trichur district was conducted during 1983.The study confined to irrigated nendran banana in Chalakudy block with the following objectives viz. to estimate cost and returns; to evaluate resource use efficiency in production; and to study the problems of banana growers. Ninetyeight holdings were selected by following the stratified two stage random sampling technique and the information was collected using a pretested schedule, through personal interview. The total cost of cultivation (cost C) of banana worked out to Rs.41814.13 per hectare. Of this, the most important item of expenditure was human labour. Average labour requirement for banana cultivation was 702.96 mandays per hectare. This was followed by expenditure on manures, fertilizers, propping materials, suckers and irrigation. All of the farmers in the locality applied chemical fertilizers though not upto the recommened level. Plant protection expenses were only 0.30 per cent of total cost. In the operationwise expenditure, manures and manuring operations demanded highest investment and formed 42.50 per cent of total cost. Propping, planting, after cultivation and irrigation, harvesting and handling and preparatory cultivation in that order were the other operations which needed investment. Plant protection operations accounted for 0.92 per cent of total cost. The average returns from banana cultivation were Rs.65011.90 per hectare. The net income from banana cultivation was Rs.23,197.77 per hectare with a benefit cost ratio of 1.55. On a per plant basis, the average cost of producing a bunch was Rs.14.31 and it gave a return of Rs.26. In the linear production function model fitted, plant population and expenditure on labour were the factors which had significant influence on the dependent variable viz. total returns. The former had a positive influence and for the latter the influence was negative. The same model was fitted for the data converted to a per plant basis. The analysis revealed that the farmers were using labour over and above the optimum level. So its use has to be restricted.